Effect of Metformin and Glimepiride Treatment on Some Biochemical Parameters in Diabetic Male Patients with Chronic Renal Failure - Abbed, Ali Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The present study was included a measurements of fasting serum glucose, total protein, potassium, and calcium levels in the sera of 25 diabetic male patients suffer from chronic renal failure; their ages range were (32-75) and compared them with 25 healthy males as control group. The aim of this study was to study the effects of antidiabetic drugs on some biochemical parameters such as fasting serum glucose, serum total protein, serum potassium and calcium. The current results demonstrated a hyperkalemia in patients and this increasing of potassium is significantly (p = 0.03), but calcium level showed no significant variations ( p>0.05 ), and serum total protein was significantly decreased in patients as compared to the controls( p = 0.0002 ).